PERSEPSI INDUSTRI TERHADAP KURIKULUM MERDEKA BELAJAR KAMPUS MERDEKA DI POLITEKNIK NEGERI BALI - Kanah; Harisal; Solihin, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The Study Program of Hospitality is one of the study programs in the Tourism Department of the State Polytechnic of Bali which has used the independent campus learning curriculum (MBKM curriculum). The MBKM curriculum has been implemented for students in class 2021 and has been running for about one semester. This study aims to describe the implications of using the MBKM curriculum in industry. To explain the implications that occur, this study uses a method with a qualitative descriptive approach. The results of the study shows that students who implement the MBKM curriculum in industry have a positive impact on industrial partners. This is proven by the activeness and enthusiasm of students during training in the industry so that industrial partners feel satisfied and are more able to give responsibility to students so that students are more competitive and flexible. In addition, students gain more than one competency from several sections they enter during training in the industry.